Communicating using storytelling method to children experienced sexual abuse and harassment - Pradanita, Vista Nurasti; Setiawati, Yunias; Yuniar, Sasanti (COUNS-EDU: The International Journal of Counseling and Education, 2021)
Every year, sexual abuse against children is increasing. Globally, it is estimated that 3-31% of children had experienced sexual abuse. This harms children, including the impact of physical injury, neurobiological impact, and psychiatric, such as depression, anxiety, eating disorders, PTSD, drug abuse, self-harm, suicidal thoughts, and attempted suicide. To help children who are victims of sexual abuse, a special approach is required to ease the communication to children. Since children communicate using symbols, thus storytelling, which is part of the Play Therapy technique, is the right method to communicate awareness to children. With an approach using the storytelling method, hopefully, children will be able to understand the very situations, recognize and express their emotions properly, and minimize the negative impact after the abuse.